中间之驿骑——中西文化在新加坡的融合与冲突 = Integration and Confliction of Chinese and Western Cultures in Singapore - Qu, Jingyi (2016)
新加坡是一個多元文化下的海上移民國家。在西方人眼中，新加坡是一個東方社會；在東方人眼中，新加坡是一個西方社會。東西方社會將新加坡視為中轉站，一個不容忽視的「小紅點」，東西方文化在新加坡吊詭的交融、衝突，形成一種獨特的文明生態。筆者借用王國維的術語「中間之驛騎」，著眼於新加坡在相當程度上已取代日本作為中西方在政治、經濟、文化、外交等多方面溝通的橋樑，而東西方文化也看似和諧地共融於新加坡。新加坡被譽為「東亞現代文明的典範」得到世界廣泛認可，政府和人民也以此為榮，「文明衝突」似乎在多元文化兼收並蓄的新加坡並不存在。但實際并非如此，新加坡人的島國性格，相對狹隘與排外，對於中西文化未能真正融合，不同宗教，不同語言，存在潛在的社會衝突，而中西方國家對新加坡也存在許多誤讀。生存、安全、成功是新加坡這個偉大小國的三個關鍵詞，絕對的靈活多變與實用主義是其內政外交的法則，實踐將繼續檢驗「新加坡派」是否能持續成功。Singapore is a migration country with multiculturalism. In the eyes of westerners, it’s an oriental society while in the eyes of Asians, it’s a Western society. Eastern and Western societies consider Singapore as a transit station. Chinese and Western cultures paradoxically blend in Singapore to form a unique ecological civilization which cannot be ignored “red dot” (statement from former Indonesian President Habibie). “Transfer-post” is a phrase from Wang Guowei in 1905 that he thought Japan translate western academic into Chinese. The paper borrows this phase, of course, not to confine to academic translation and unilateral impact studies, while to focus on a considerable extent that Singapore has replaced Japan as a bridge in politics, economy, culture, diplomacy, etc. between China and Western countries and Chinese and Western cultures were integrated amazingly. However, real social status in Singapore proves Samuel Huntington’s Theory of Clash of Civilization potentially exist because of cultures’ misunderstanding and reflect in all aspects of social lives. Lee Kuan Yew’s three words, survival, security and success have become key words of the great little country. Indeed, powerful flexibility and absolute pragmatism form a successful paradigm, so-called “Singapore PI”, which will be tested by future practice.